Recent Clinical Results of Endoscopic Bariatric Therapies as an Obesity Intervention - Fateh Bazerbachi; Eric J. Vargas Valls; Barham K. Abu Dayyeh (Korean Society of Gastrointestinal Endoscopy, 2017)
Despite advances in lifestyle interventions, anti-obesity medications, and metabolic surgery, the issue of health burden due to obesity continues to evolve. Interest in endoscopic bariatric techniques has increased over the years, as they have been shown to be efficacious, reversible, relatively safe, and cost effective. Further, these techniques offer a therapeutic window for some patients who may otherwise be unable to undergo bariatric surgery. This article aims to review the literature on the safety and efficacy of currently offered endoscopic bariatric techniques, as well as those that are in the pipeline of end-development and regulatory approval.